Long-term maintenance and complications of fixed dental prostheses - Binhuraib, Haitham Mohammed; Alqarni, Sundus Saad; Mohsen, Nagam Mohammed; Alharbi, Abeer Ahmad; Alghamdi, Ahmed Ibrahim; Almotairi, Adeeb Maseer; Alhussain, Abdulrahman Hussain; Felemban, Rahaf Ayman; Alzahrani, Anwar Salem; Eyouni, Ehdaa Sameer; Alhajjaji, Razan Ibrahim (International Journal Of Community Medicine And Public Health, 2024)
Fixed dental prostheses (FDPs), commonly known as dental bridges, play a pivotal role in restorative dentistry, offering patients a means to regain oral function and aesthetics in cases of tooth loss. These prosthetic devices, anchored to natural teeth or dental implants, bridge the gap created by missing teeth, improving chewing, speech, and smile aesthetics. However, the successful deployment of FDPs requires not only their initial placement but also long-term maintenance and an understanding of potential complications. Effective oral hygiene, regular dental surveillance, and professional dental cleanings are essential for preserving FDP longevity. Vigilance is crucial as FDPs, while resistant to cavities themselves, can pose challenges in cleaning around abutment teeth. Complications, including dental caries, periodontal issues, crown or bridge fractures, abutment tooth deterioration, aesthetic alterations, sensory sensitivity, and even prosthetic failure, are potential concerns. Timely intervention and preventive measures are key to addressing these issues. When complications arise, dental practitioners can often repair superficial problems like crown fractures. Profound or recurrent complications may require more extensive interventions, such as fabricating a new bridge or considering alternative restorative options like dental implants or removable partial dentures. By embracing these principles of maintenance and management, patients can optimize the durability and functionality of their FDPs while minimizing associated risks, ensuring a healthy and confident smile for years to come.